Global overview of the risk linked to the Bacillus cereus group in the egg product industry: identification of food safety and food spoilage markers34048 - Techer,C.; Baron,F.; Laurence Delbrassinne; Belaid,R.; Brunet,N.; Gillard,A.; Gonnet,F.; Cochet,M.F.; Grosset,N.; Gautier,M.; Mirjana Andjelkovic; Lechevalier,V.; et al. (J.Appl.Microbiol., 2014)
AIMS: To evaluate the food safety and spoilage risks associated with psychrotrophic Bacillus cereus group bacteria for the egg product industry and to search for relevant risk markers. METHODS AND RESULTS: A collection of 68 psychrotrophic B. cereus group isolates, coming from pasteurized liquid whole egg products, was analysed through a principal component analysis (PCA) regarding their spoilage and food safety risk potentials. The principal component analysis showed a clear differentiation between two groups within the collection, one half of the isolates representing a safety risk and the other half a spoilage risk. CONCLUSIONS: Relevant risk markers were highlighted by PCA, that is (i) for the food safety risk, the presence of the specific 16S rDNA-1m genetic signature and the ability to grow at 43 degrees C on solid medium and (ii) for the spoilage risk, the presence of the cspA genetic signature. SIGNIFICANCE AND IMPACT OF THE STUDY: This work represents a first step in the development of new diagnostic technologies for the assessment of the microbiological quality of foods likely to be contaminated with psychrotrophic B. cereus group bacteria
Keywords: a; aims; analysi; analysis; article; assessment; at; Bacillus; Bacillus cereus; bacteria; de; Development; electronic; ET; food; Food Safety; Foods; France; Genetic; global; Group; i; identification; im; Impact; Industries; Industry; IS; journal; Marker; Markers; MEDIA; method; methods; microbiologie; ON; Principal component; Principal Component Analysis; PRODUCTS; Quality; result; results; risk; risks; SAFETY; SB - IM; Science; Search; specific; study; technology; work